Effect of Mn Doping on the Electronic and Magnetic Properties of Full Heusler Alloy Co2FeSi - Pokhrel, Pramila Kumari; Kaphle, Gopi Chandra (Journal of Lumbini Engineering College, 2022)
Heusler compounds are one of the largest families of ternary intermetallics with broad range of applications. In this work, we inspected the electronic and magnetic properties of full Heusler alloy Co2FeSi and the effect induced by doping Mn atom on those properties. We employed plane wave pseudo-potential method based on DFT framework implemented in Quantum ESPRESSO code using PBE type of functional for exchange correlation energy. The calculation demonstrates that Co2FeSi exhibits metallic nature in the majority spin state and semi-conducting nature in minority spin state with indirect energy gap of ≈ 0.132 eV and shows chances of weakened half-metallicity as indicated by the presence of band gap below fermi level. The calculated total magnetic moment is 5.44 μB/cell which is found to be deviated from Slater-Pauling rule M = NV − 24 for full Heusler compounds. The site selection for doping was based on the empirical rule for atomic occupation established for Heusler alloys and the calculation of formation energy. The calculation of formation energy at B and D site showed B site as more favorable for doping for both 25% and 50% concentration. At 25% Mn concentration, calculation shows Co2FeSi has typical metallic behavior for spin-up electrons, but semi-conducting behavior with decreased gap below fermi level for spin-down electrons showing no half-metallicity whereas for 50% Mn concentration the gap gets broadened by 0.089645 eV. The calculated magnetic moment for 25% and 50% Mn doping is 21.93 μB/cell and 21.69 μB/cell respectively. Our calculation depicts that the chances of half-metallicity decreases for 25% concentration of Mn atom and increases for 50% Mn concentration.